Analisis Pengendalian Internal Dalam Pengelolaan Persediaan Obat Pada Apotek Di Pekanbaru - Dian Saputra; Abrar (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
In the world of health, the existence of pharmacies is very important in the community to support the need for the supply of medicines. The phenomenon of poor management of medicine supplies still often occurs in pharmacies such as damaged medicine, counterfeit and expired medicine, so that it affects people who buy and causes losses. This study aims to obtain an overview and assess the effectiveness of the internal control system in managing medicine supplies at pharmacies in Pekanbaru. Methods This research uses a qualitative study approach with an analysis tool for components of the Internal Control System from COSO and uses the Miles & Huberman data analysis method. The results of this study indicate that there are still pharmacies that have minimal management of medicine supplies, resulting in the sale of expired medicine, no destruction of medicine, the use of inventory systems outside the applicable regulations.